A study on the effects of compost from ipil-ipil leaves (Leucaena leucocephala) and rice straw (oryza sativa) on the growth and productivity of pechay (Brassica juncea. - Polido, Wilfredo T
A study on the effect of leguminous compost from ipil-ipil was conducted from January 11 to February 15, 1992 at Barangay Tabuc Suba Jaro City. Two experimental treatments namely, ipil-ipil compost and rice-straw compost, were used. A control was provided to serve as a basis of comparison., The results of the study showed that the application of compost tended to increase the yield of pechay, number of, height of plants and improve leaf appearance. Although there was notable increase in nuber of and improvement in leaf coloration with rice -straw compost, statistical analysis did not show significant difference with control. Statistical analysis using ANOVA followed by DMRT at 95 level of significance revealed that differences among ipil-ipil treatment and the other set-ups in all parameters used were significant. Thus, application of ipil-ipil compost significantly improved the growth and productivity of pechay compared to rice-straw compost and plain soil.